Formulae to use:
sin(A+B)= sinAcosB + sinBcosA
cos(A+B)=cosAcosB - sinAsinB
Consider expression
$E= \sqrt 2 (\frac{1}{\sqrt 2}\cos x + \frac{1}{\sqrt 2}\sin x)$
But we have $\sin \frac{\pi}{4}= \cos \frac{\pi}{4}=\frac{1}{\sqrt{2}}$
Thus,
$E=\sqrt{2} (\sin \frac{\pi}{4} \cos x+ \cos \frac{\pi}{4} \sin x)$
$E =\sqrt{2} (\sin (\frac{\pi}{4})+ x)$
Similarly you can simplify the denominator.
Thus we we have to simply find:
$ \frac{d}{dx} \bigg( \frac{ \sqrt{2} (\sin (\frac{\pi}{4})+ x)}{\sqrt{2} (\cos (\frac{\pi}{4})+ x)} \bigg)$
$= \frac{d}{dx} ( tan((\frac{\pi}{4}+ x))$
$= \sec ^2 (\frac{\pi}{4})+ x)$